In-situ synthesized V2CTx MXene-based immune tag for the electrochemical detection of Interleukin 6 (IL-6) from breast cancer cells - Vessella, Theadora; Zhang, Hui; Zhou, Zhiru; Cui, Feiyun; Zhou, Hong Susan (Biosensors & bioelectronics, 2023)
Interleukin-6 (IL-6) is a proinflammatory cytokine with a critical role in immune regulation and treatment of many diseases, including breast cancer. Herein, we developed a novel V2CTx MXene-based immunosensor for rapid and accurate IL-6 detection. The chosen substrate was V2CTx, a 2-dimensional (2D) MXene nanomaterial with excellent electronic properties. Prussian blue (Fe4[Fe(CN)6]3), used for its electrochemical properties, and spindle-shaped gold nanoparticles (Au SSNPs), used to combine with antibodies, were in-situ synthesized on the surface of the MXene. The in-situ synthesis ensures a firm chemical connection compared to other tags formed by a less stable physical absorption. Inspired by a sandwich ELISA test, the modified V2CTx tag was captured by the electrode surface with cysteamine to detect the analyte, IL-6, after being attached with a capture antibody (cAb). Benefiting from an increased surface area, an enhanced charge transfer rate, and a firm connection of the tag, this biosensor exhibited excellent analytical performance. The high sensitivity, high selectivity, and wide detection range covering the IL-6 level of both healthy individuals and breast cancer patients were obtained to meet clinical demands. Herein, this V2CTx MXene-based immunosensor is a potential therapeutic and diagnostic point-of-care alternative to routine ELISA IL-6 detection methods.